CRITICAL DISCOURSE IN THE FOLKTALE 'MALIN KUNDANG': AN ANALYSIS OF MYTHOLOGY AND POWER IN MINANGKABAU CULTURE - St Syahriati; Jufri (LLDIKTI Wilayah X, 2025)
Critical Discourse in the Malin Kundang Folktale: An Analysis of Mythology and Power in Minangkabau Culture. This study aims to analyze power relations, the naturalization of values, and the construction of mythology in the Malin Kundang folktale. The study uses a qualitative approach with a Critical Discourse Analysis design that combines the perspectives of power–discourse and mythological theory. The data in the form of story texts are analyzed through stages of reduction, categorization, and interpretation of narratives that represent mother–child relations and symbols of punishment. The results of the study indicate that disobedience is constructed gradually through changes in social status and identity conflicts; the mother's authority is legitimized as the moral center of the family; and the transformation into stone functions as a mythologization mechanism that naturalizes the norm of obedience. The conclusion of the study confirms that folktales act as discursive practices that reproduce power relations and shape moral subjects in Minangkabau culture.